2005
DOI: 10.1021/es0506556
|View full text |Cite
|
Sign up to set email alerts
|

Polyfluoroalkyl Compounds in Free-Ranging Bottlenose Dolphins (Tursiops truncatus) from the Gulf of Mexico and the Atlantic Ocean

Abstract: Polyfluoroalkyl compounds (PFAs) have been used for decades in industrial and commercial products and are now detected worldwide. Concentrations of two major PFA groups, carboxylic acids (PFCAs) and sulfonic acids (PFSAs), were assessed in plasma of bottlenose dolphins from the Gulf of Mexico (Sarasota Bay, FL) and the Atlantic Ocean (Delaware Bay, NJ, Charleston, SC, Indian River Lagoon (IRL), FL, and Bermuda). Eight PFAs were detected in the plasma of all dolphins. Perfluorooctane sulfonate (PFOS) was the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(157 citation statements)
references
References 40 publications
13
142
2
Order By: Relevance
“…[17] Polar bears showed the highest amounts of PFHxS among mammals, but PFBS was not analysed (Table 1). Fluorotelomer saturated and unsaturated carboxylates (FTCAs and FTUCAs) were found in very low concentrations in several marine mammal species such as ringed seals (o4.6 ng g À1 ww) [71] and dolphins from the US Atlantic Ocean coast (o1.4 ng g À1 ww), [92] but they were not detected in polar bears from the Canadian Arctic [78] and in dolphins and porpoises from South China and India. [84,88] The presence of those precursor compounds supports the hypothesis that atmospheric FTOHs are a source of PFCAs as FTOH can degrade via atmospheric oxidation to FTCAs and FTUCAs.…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Polar bears showed the highest amounts of PFHxS among mammals, but PFBS was not analysed (Table 1). Fluorotelomer saturated and unsaturated carboxylates (FTCAs and FTUCAs) were found in very low concentrations in several marine mammal species such as ringed seals (o4.6 ng g À1 ww) [71] and dolphins from the US Atlantic Ocean coast (o1.4 ng g À1 ww), [92] but they were not detected in polar bears from the Canadian Arctic [78] and in dolphins and porpoises from South China and India. [84,88] The presence of those precursor compounds supports the hypothesis that atmospheric FTOHs are a source of PFCAs as FTOH can degrade via atmospheric oxidation to FTCAs and FTUCAs.…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…[85] Contrarily, Smithwick et al found increasing PFOS and C 9 -C 14 PFCA concentrations in male polar bears up to an age of six. [99] Higher concentrations of PFOS in pups than in adults were also found in sea otters from Alaska, [74] Baikal seals from Russia, [72] bottlenose dolphins from the Atlantic Ocean, [92] harbour seals from the north-west Atlantic Ocean [83] and the German Bight, [76] harbour porpoises from the southern North Sea [97] and elephant seals from the Antarctic. [103] This was explained by higher rates of elimination in adults, [73] different consumption of different contaminated food, [76] and PFC transfer from mothers to their offspring through milk or placenta after parturition.…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…Papillomavirusassociated orogenital papillomas have been described in other marine mammal species (Van Bressem et al 1996, 2007a, Bossart et al 2002, Ghim et al 2014). In our earlier study from 2003 to 2005, orogenital papillomas were described for the first time in association with virions ultrastructurally suggestive of a herpesvirus (Bossart et al 2005), and later with infection associated with the first reported American dolphin papillomavirus (Rehtanz et al 2006(Rehtanz et al , 2010. More recently, co-infection with a papillomavirus and herpesvirus was reported in genital papillomas from HERA dolphins (Rehtanz et al 2012).…”
Section: Discussionmentioning
confidence: 87%
“…In instances when a tooth was unobtainable, age was estimated from total body length ranges established for the species (Geraci & Lounsbury 2005). For this study, adults were defined as dolphins 6 yr of age or older and subadults from 3.5 to 5.9 yr, as described previously (Bossart et al 2005. Dolphin calves were not included in the study, as this age group was not permitted to be captured under capture permit restrictions.…”
Section: Methodsmentioning
confidence: 99%
“…PFOS and PFCA concentrations detected in the plasma of bottlenose dolphins sampled in Charleston, SC (2003SC ( -2004 represent some of the highest concentrations reported in marine mammals (Houde et al, 2006b;Houde et al, 2005). Charleston, SC is centrally located within the southeast region of the United States.…”
Section: Introductionmentioning
confidence: 99%